Differences in cNOS/iNOS Activity during Resistance to Trypanosoma cruzi Infection in 5-Lipoxygenase Knockout Mice - Carolina Panis; Vanessa Jacob Victorino; Vera Lúcia Hideko Tatakihara; Rubens Cecchini; Luiz Vicente Rizzo; Lucy Megumi Yamauchi; Sueli Fumie Yamada-Ogatta; Marli Cardoso Martins-Pinge; Phileno Pinge-Filho (Mediators of Inflammation)
Infection with the protozoan Trypanosoma cruzi causes Chagas disease and consequently leads to severe inflammatory heart condition; however, the mechanisms driving this inflammatory response have not been completely elucidated. Nitric oxide (NO) is a key mediator of parasite killing in T. cruzi-infected mice, and previous studies have suggested that leukotrienes (LTs) essentially regulate the NO activity in the heart. We used infected 5-lipoxygenase-deficient mice (5-LO−/−) to explore the participation of nitric oxide synthase isoforms, inducible (iNOS) and constitutive (cNOS), in heart injury, cytokine profile, and oxidative stress during the early stage of T. cruzi infection. Our evidence suggests that the cNOS of the host is involved in the resistance of 5-LO−/− mice during T. cruzi infection. iNOS inhibition generated a remarkable increase in T. cruzi infection in the blood and heart of mice, whereas cNOS inhibition reduced cardiac parasitism (amastigote nests). Furthermore, this inhibition associates with a higher IFN-γ production and lower lipid peroxidation status. These data provide a better understanding about the influence of NO-interfering therapies for the inflammatory response toward T. cruzi infection.